EFFICIENCY OF TUBERCULOSIS DIAGNOSTICS IN CHILDREN'S POPULATION - B.P. SHARIPOV; D.M. YUSUPDZHAANOVA; D.A. MELIKOV; A.M. ISLOMOV (Avicenna Tajik State Medical University, 2018)
Objective: Assisting to medical workers both of phthisiology institutions and primary health care in identifying and timely diagnosing tuberculosis (TB) in children. Methods: The data of state statistics analyzed on the total number of detected cases of tuberculosis and the number of identified cases of tuberculosis among children in the Republic of Tajikistan for 2013-2017. In addition, during the same period studied the data of all patients treated by tuberculosis at the Dushanbe City Children's Tuberculosis Hospital. Results: The ratio of active TB among children and adults in the period 2013-2017 ranged from 10.8% to 11.8%. The ratio of the number of sick children with multiple drug resistance of TB (MDR) to the total number of cases of child TB in the same period showed a tendency to increase from 4.3% to 6.5%. In 2017, the incidence of pulmonary TB with MBT (+) was 54.8%, including 16% for children aged 0-4 years, 37.5% for 5-14 years, and 69.3% for children aged 15-17 years. Conclusion: The tuberculosis process in children has its own features. Timely diagnostics, including the induced collection of bronchial secretion and application of the latest genetic technologies, greatly accelerates the verification process of the diagnosis and detection of both sensitive and resistant forms of Mycobacterium tuberculosis. There is an increase in the primary drug resistance of TB among children, which again confirms the need for a thorough examination of all contact persons.